Chemotherapy-induced peripheral neuropathy. Part II: Prevention - Brzeziński, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2012)
The incidence of chemotherapy-induced peripheral neuropathy (CIPN) in the population of cancer patients is estimated at 3–7% in cytostatic monotherapy and as high as 38% in the case of polytherapy. While testing drugs that may reduce the damage to the peripheral nervous system, particular attention should be paid to their protective action against the severe and painful complication in the patient. Another aspect, perhaps a more important one, is the confidence that application of preventive drugs will not exert a significant impact on progression of the neoplastic disease or the effectiveness of the causal treatment. Many drugs have been tested for prevention of CIPN; however, none of them have thus far been irrefutably proven to possess preventive properties. No guidelines on chemotherapy-induced peripheral neuropathy preventive action have been established, either. This article is an attempt to present reports from the available literature about the possibilities of prevention of CIPN.